Alumbrado público del polideportivo Ospina Pérez infraestructura y red eléctrica (2021)
The purpose of this degree work is to design the public lighting system for the sports center Ospina Pérez in the city of Cúcuta Norte de Santander, applying the latest trends in public lighting for sports fields that are being developed in the country, such as LED-type technologies, which are being used massively in recent years, seeking to reduce the negative environmental impact through significant improvements in energy efficiency. The design focuses on the projection of the infrastructure and the electrical network for the public lighting of the sports center using Led technology and applying the regulations of the RETIE and RETILAP.